Residency training for minimally invasive surgery - CAMPOS,MARCELO ESTEVES CHAVES (2022)
ABSTRACT Objective: to develop a training program in minimally invasive surgery, based on simulation and with an emphasis on the acquisition of laparoscopic competences. Methods: this was a prospective, observational study carried out at a university hospital in Belo Horizonte, Brazil, between April 2020 and January 2021. We recruited residents of surgical specialties for structured, progressive training according to instructional principles to promote learning, such as motivation, activation, demonstration, application, and integration. We filmed the skill tests at the program’s beginning, middle, and end, which were then anonymously evaluated by a surgical education expert. Individual performances were scored using the global assessment tools “GOALS” and “specific checklist for suture”. At the end, all participants received individual feedback and completed a questionnaire to assess the impact of training on the Kirkpatrick model. Results: 43 residents completed the program. The evolution of performances was evident and grew between tests. The average achievements were 29% in the initial test, 43% in the intermediate test, and 88% in the final test, with significant differences between all mean scores, with H=97.59, GL=2, p<0.0001. The program evaluation and learning perceptions were excellent, but only 10.7% of residents felt fully capable of performing unsupervised, low-complexity laparoscopic surgery at the end of training. Conclusions: the training program developed in this study proved to be feasible and promising as a strategy for teaching laparoscopic surgery.